Trends of Primary Renal Tumors in Adult Pakistani Population. A Single Center Study - Fatima, Mariam; Babar, Kanwal; Batool, Hira; Yasin, Rafeya; Chughtai, Omar; Bashir, Azra (Biological and Clinical Sciences Research Journal, 2025)
Renal cell carcinoma (RCC) represents a heterogeneous group of tumors with diverse histopathological subtypes and clinical behaviors. Locoregional studies are essential to understand various subtypes, prevalence, demographic patterns, and staging profiles for effective disease management. Objective: The purpose of this study is asses the histological spectrum, demographic characteristics, and pathological staging of renal tumors diagnosed at a specialized diagnostic center in Pakistan. Methods: A cross-sectional analysis was conducted at Chughtai Lab from March 2023 to September 2024. A total of 267 cases of renal tumors, including both malignant and benign entities, were reviewed. Tumors were classified according to the 2022 WHO Classification. Pathological staging was performed using the AJCC 8th edition TNM system. Data were analyzed using SPSS v26.0, with descriptive statistics for frequency, percentage, and mean age calculations. Results: Clear cell RCC is the most prevalent subtype (61.79%), followed by papillary RCC (8.61%) and chromophobe RCC (4.86%). Rare malignant tumors account for 5.61% of cases. Among benign tumors, oncocytoma is the most common (4.1%). The mean age of patients is 53.8 years, with a male-to-female ratio of 1.47:1. Pathological staging reveals pT1b (30.00%) followed by pT3a (22.91%) and pT2a (20.83%) are the most frequent stages among 240 patients. Conclusion: Clear cell RCC remains the predominant renal tumor subtype in our population. Most cases are diagnosed at early pathological stages, indicating improved detection trends. This study contributes essential locoregional data that support global epidemiological patterns and highlights the importance of accurate histopathological classification for optimal patient management.